The Islamization of Science: The Intellectual Response of Indonesian Muslims to the Integration of Religion and Science in the Millennial Era - Muhamad Aufa Firzatullah; Arditya Prayogi; Salwa Durrotun Nashah; Nur Rosidah (Averroes: Journal for Science and Religious Studies, 2026)
Research Background: This article examines how Indonesian Muslim intellectuals respond to the discourse of Islamization of knowledge in the millennial era, particularly in connecting religious values with the development of modern science. The study addresses three main questions: how Islamic teachings are positioned in relation to scientific progress, what methodological approaches are proposed by Muslim thinkers, and how relevant these perspectives are for contemporary education. Methods: Using a qualitative descriptive method and literature-based analysis, this research explores key arguments, conceptual frameworks, and patterns of thought found in recent scholarly works. Key Findings: The findings indicate that Indonesian Muslim intellectuals generally adopt integrative, critical, and dialogical approaches toward the relationship between religion and science. Islamization of knowledge is not understood as a rejection of modern science, but as an effort to embed ethical, moral, and spiritual values within scientific development. Contribution: This article contributes to current scholarship by mapping contemporary intellectual positions in Indonesia and clarifying the diversity of responses to the science–religion relationship. Conclusion: It concludes that Islamization of knowledge can serve as a productive framework for strengthening moral awareness while maintaining the critical and open character of scientific inquiry.